Peer Review - Team, Editorial (Journal of Medicine and Health, 2021)
We would like to thank our peer reviewers for the precious contributions in providing clinical, scientific, and methodological expertise for JMH Volume 3 Number 2 August 2021. We appreciate every thoughtful review of submitted manuscripts and for making important contributions to improve the scientific quality of articles published in JMH. We listed the names in alphabetical order. Abram Pratama, dr., Sp.PD. Adhi Kristianto Sugianli, dr., Sp.PK(K), M.Kes. Prof. Dr. Asep Sukohar, dr., M.Kes. Deta Tanuwidjaja, dr., Sp.KFR., AIFO-K. Dimas Erlangga Luftimas, dr., M.Kes., Sp.GK. Edwin Setiabudi, dr., Sp.PD-KKV, FINASIM Fenny, dr., Sp.PK., M.Kes. Ginna Megawati, dr., M.Kes. Grace Puspasari, dr., M.Gizi Dr. Guswan Wiwaha, dr., MM. Dr. Hana Ratnawati, dr., M.Kes., PA(K) Juwita Ningsih, drg., M.Sc. Dr. Meilinah Hidayat, dr., M.Kes. Santun Bhekti Rahimah, dr., M.Kes. The, Fransiska Eltania, dr., M.Kes., A3M. Teresa Lucretia, dr., M.Kes. Prof. Wahyuni Lukita Atmadja, dr., Ph.D. Yenni Limyati, dr., S.Sn., Sp.KFR. Yuktiana Kharisma, dr., M.Kes.